Answer:
72.22
Step-by-step explanation:
Y = 12.1% x 13 + 351
y= 0.012 x 13 + 351
y= 1.573 + 351
y= 352.573 or $352.6
Answer:
C
Step-by-step explanation:
(4x-5) - (3x-10) = ?
(4x-5) - 1 (3x-10) = ? DISTRIBUTE THE INVISIBLE -1 to (3x-10)
Turns into: 4x - 5 - 3x + 10
Which equals: x + 5
Answer:
I cant Im sorry
Step-by-step explanation:
We can begin by rewriting the problem:
4(2x + 5) + 2x + 3 = -11
Let’s solve in steps.
1. Distribute
8x + 20 + 2x + 3 = -11
2. Combine like terms
10x + 23 = -11
3. Subtract 23 from both sides
10x + (23 - 23) = -11 - 23
10x = -34
4. Divide both sides by 10
10 / 10 = 1 (or x)
-34 / 10 = -3.4
Therefore, x = -3.4.